Spatial and Destination Dynamics of Indonesian Migrant Workers from Papua Province: Regional Origin Patterns and International Labor Mobility Trends, 2023–2025 - Ronald; Muktamar Umakaapa; Febry Rahmadhani Suradji; Pricilya Margaretha Warwuru (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: International labor migration plays a crucial role in addressing economic disparities and limited employment opportunities, particularly in peripheral regions such as Papua Province, which remains underrepresented in migration studies. Objectives: This study aims to identify spatial patterns of migrant worker origins and analyze changes in destination countries during the 2023–2025 period. Method: A quantitative descriptive approach is employed using secondary data from official statistics. The analysis combines spatial distribution to examine regional patterns and temporal trend analysis to capture changes in destination dynamics. Results: The findings show that migration flows are relatively low but fluctuating, with a decline in the dominance of Papua New Guinea as a traditional destination. In contrast, Japan exhibits a significant increase and becomes a leading destination in 2025. New destinations such as Türkiye and Hong Kong also emerge, indicating diversification. Spatially, migrant workers are highly concentrated in urban areas, particularly Kota Jayapura, while remote regions show minimal participation. Conclusion: Migration patterns are becoming more diversified but remain unevenly distributed, highlighting the need for inclusive policies, improved access to migration services, and enhanced skills development. Keywords: migration, Papua, labor mobility, spatial, diversification